Assessment of the level of adaptation and disadaptation of athletes body to physical loads - Yusupova, Y. N.; Khadjimetov, A. A. (Global Journal of Medical research: K Interdisciplinary, 2018)
Data of blood indicators, oral fluid and lactate in rowers on canoes, canoes at rest and under the influence of complex of physical activities of different directions are given in this study. The study involved canoeists and canoes (21 athletes, men and women, aged 19-25 years), who are at the general preparatory stage of the preparatory training period. The dynamics of the content of histamine in the oral fluid and blood as well as the content of lactate in the blood were investigated. The results of the study indicate the degree of adaptation of the athlete to physical activity. Keywords: sport,